1998
DOI: 10.1159/000027606
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Induced Expression of Reactive Oxygen Species and Peroxynitrite in the Guinea Pig Vestibular Organ

Abstract: The purpose of this study was to investigate the occurrence of reactive oxygen species and peroxynitrite in the vestibular organ of the guinea pig following inoculation with bacterial lipopolysaccharide (LPS). The animals were injected transtympanically with 1 mg of LPS 24 h after the intraperitoneal injection of 0.1 mg LPS. Forty-eight hours after the inoculation, varying degrees of degeneration of the vestibular end organs were observed. Immunohistochemical study revealed immunoreactivity to xanthine oxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…The formation of superoxide in the vestibular end organs after inoculation with LPS has been documented by the use of xanthine oxidase immunohistochemistry [11]. The present investigation, which confirmed a marked protective role of SOD against the action of LPS upon both the caloric responses and inner ear morphology, thus supports the view that reaction of NO with superoxide is indeed involved in ototoxicity.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The formation of superoxide in the vestibular end organs after inoculation with LPS has been documented by the use of xanthine oxidase immunohistochemistry [11]. The present investigation, which confirmed a marked protective role of SOD against the action of LPS upon both the caloric responses and inner ear morphology, thus supports the view that reaction of NO with superoxide is indeed involved in ototoxicity.…”
Section: Discussionsupporting
confidence: 86%
“…10 9 M -1 W s -1 ) to form what is a highly oxidizing and cytotoxic molecular species, compared with NO or O 2 - [14]. In fact, formation of peroxynitrite in the LPS-inoculated vestibular organ is substantiated by the immunohistochemical study using a specific antinitrotyrosine antibody, which clearly demonstrated intense staining of the apical border of the sensory cells, of vestibular fluid transporting cells, and of ES epithelial cells [11]. Several forms of evidence revealed that nitrotyrosine was produced by peroxynitrite in a variety of proteins through a reaction catalyzed by heavy metals such as iron and copper [14].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A considerable amount of evidence has recently accumulated suggesting that nitric oxide (NO) and its related reactive oxygen species (ROS) play a crucial role in certain inner ear disorders, such as acoustic trauma [1], labyrinthitis [2][3][4], aminoglycoside [5][6][7][8][9] and cisplatin ototoxicity [10], and endolymphatic hydrops [11]. The involvement of ROS and their importance in hair cell death caused by aminoglycosides is suggested by a number of studies that have demonstrated a prophylactic effect of antioxidants [6,7,12].…”
Section: Introductionmentioning
confidence: 99%
“…The other important free radical, NO, also plays an important part in inner ear toxicity. In the pathological condition, overproduction of NO, resulting in formation of peroxynitrite, can induce morphological and functional inner ear disorders [3,4,9].…”
Section: Introductionmentioning
confidence: 99%